2012
DOI: 10.1016/j.ijgo.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of surgical outcomes between laparoscopic and open myomectomy in Southern Taiwan

Abstract: Compared with OM, LM was found to be associated with shorter surgical time and less blood loss, but there was no difference in the rate of complications or recurrence between the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
2
7
2
Order By: Relevance
“…Compared with TAM, the feasibility and safety of LM has been demonstrated . However, the effectiveness of LM on fertility has yet to be clarified.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared with TAM, the feasibility and safety of LM has been demonstrated . However, the effectiveness of LM on fertility has yet to be clarified.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with TAM, the feasibility and safety of LM has been demonstrated. 16 However, the effectiveness of LM on fertility has yet to be clarified. The results of our study are in line with previous publications, which found that the birth control time is longer after TAM than after LM, 17 and that the overall cumulative pregnancy rates, live birth rates and obstetric complications have no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we observed that estimated blood loss (EBL) was twice as high compared to the previous studies mentioned [17][18]. Our study demonstrated an EBL with a median of 500 mL as compared to 200 mL in Barakat, 200 mL in Sangha, and 150 mL in Chang [17][18][19]. The reason for the high value in our study is that one of our patients lost 3000 mL in the procedure, and six procedures also reported a 2000 mL loss, which led to the high values in our analysis.…”
Section: Discussioncontrasting
confidence: 54%
“…In the current study, we found that the median duration of the surgery is 92 min. Compared to other studies, this was higher in Barakat, Chang, and Sangha, with 126 min, 120 min, and 127.5 min, respectively [17][18][19]. The time from the incision to closure is defined as actual surgical time.…”
Section: Discussionmentioning
confidence: 83%
“…The LM is generally associated with less morbidity (e.g. less postoperative pain, rapid recovery, shorter hospital stay, smaller incisions) as compared with laparotomy [8, 11, 12], but the intraoperative blood loss remains a critical challenge in LM [6, 1316]. …”
Section: Introductionmentioning
confidence: 99%